Self-lubricating conductive fiber and preparation method thereof
By plating a metal-based self-lubricating coating on the surface of the carbon fiber matrix, the problem of lacking fiber materials with both conductivity and self-lubricating functions in the prior art is solved, and the anti-wear and friction reduction effects of the fiber materials during friction and wear are achieved, while maintaining good conductivity.
Patent Information
- Application Number
- CN202510104294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-04
AI Technical Summary
No fiber materials that have both conductivity and self-lubricating functions have been found in the prior art.
By plating a metal-based self-lubricating plating on the surface of the carbon fiber matrix, the plating layer contains metal and self-lubricating material to form self-lubricating conductive fibers.
It realizes that fiber materials have anti-wear and friction reduction effects during friction wear, while maintaining good conductivity.
Smart Images

Figure CN119553494A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional fibers, and in particular to a self-lubricating conductive fiber and a preparation method thereof. Background Art
[0002] Carbon fiber has excellent mechanical properties such as specific strength and specific modulus, and its low density, corrosion resistance, high temperature resistance, easy processing, and designability make it widely used in aerospace, military, energy, sporting goods, automotive industry, rail transportation, and building reinforcement. It is known as the "king of new materials". However, in some scenarios, carbon fiber lacks the functionality that matches the application end.
[0003] So far, there is no report on fiber materials with both electrical conductivity and self-lubricating functions. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a self-lubricating conductive fiber and a preparation method thereof, which has both conductive and self-lubricating functions.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The invention provides a self-lubricating conductive fiber, comprising a fiber matrix and a metal-based self-lubricating coating coated on the surface of the fiber matrix; the metal-based self-lubricating coating comprises metal and a self-lubricating material.
[0006] Preferably, the fiber matrix comprises carbon fibers.
[0007] Preferably, the metal includes one or more of nickel, copper, silver, aluminum and gold.
[0008] Preferably, the self-lubricating material includes one or more of graphite, molybdenum disulfide, tungsten disulfide and polytetrafluoroethylene.
[0009] Preferably, the mass of the metal-based self-lubricating coating is 20-60% of the mass of the self-lubricating conductive fiber; the mass of the self-lubricating material is 0.5-2% of the mass of the self-lubricating conductive fiber.
[0010] The present invention provides a method for preparing the self-lubricating conductive fiber described in the above scheme, comprising the following steps: The fiber matrix is placed in a metal plating solution containing a self-lubricating material and electroplated to obtain the self-lubricating conductive fiber.
[0011] Preferably, before the electroplating, the fiber matrix is also pre-treated, and the pre-treatment includes: sequentially burning and cleaning the fiber matrix with a cleaning agent.
[0012] Preferably, the calcination temperature is 400-600° C., and the holding time is 3-10 min; the calcination is carried out under protective gas conditions.
[0013] Preferably, in terms of mass percentage, the cleaning agent includes 0.05-0.5% of a cationic surfactant, 0.5-2% of an organic amine, 0.5-6% of an alcohol and / or ether and / or alcohol ether, and the remainder is water.
[0014] Preferably, the cationic surfactant includes dodecylquinolinium bromide; the organic amine includes polyethylene polyamine and / or diglycolamine; the alcohol includes 2-amino-2-ethyl-1,3-propanediol; the alcohol ether includes dipropylene glycol monomethyl ether; and the ether includes one or more of diether, aromatic ether and cyclic ether.
[0015] The present invention provides a self-lubricating conductive fiber, comprising a fiber matrix and a metal-based self-lubricating coating coated on the surface of the fiber matrix; the metal-based self-lubricating coating comprises metal and a self-lubricating material. There is no fiber with both conductive and self-lubricating functions in the prior art. The coating of the present invention is a metal substrate with good conductivity. By adding a self-lubricating material to the coating, the fiber is given a self-lubricating function. The fiber material of the present invention has both conductive and self-lubricating functions.
[0016] The present invention provides a method for preparing the self-lubricating conductive fiber described in the above scheme, wherein a metal-based self-lubricating coating is formed by adding a self-lubricating material into a plating solution.
[0017] Furthermore, the present invention can improve the bonding force between the fiber matrix and the metal-based self-lubricating coating by pre-treating the fiber matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the structure of the self-lubricating conductive fiber of the present invention, wherein: 1-1 is a fiber matrix, 1-2 is a metal-based self-lubricating coating, and 1-3 is a self-lubricating material in the metal-based self-lubricating coating; Figure 2 It is a schematic diagram of the preparation process of the self-lubricating conductive fiber in an embodiment of the present invention, wherein: 1-fiber pay-off device, 2-fiber flattening device, 3-high temperature oven, 4-first transmission guide roller, 5-cleaning tank, 6-second transmission guide roller, 7-first water washing tank, 8-third transmission guide roller, 9-negative electrode of DC power supply, 10-electroplating tank, 11-fourth transmission guide roller, 12-second water washing tank, 13-drying oven, 14-winding device. DETAILED DESCRIPTION
[0019] The invention provides a self-lubricating conductive fiber, comprising a fiber matrix and a metal-based self-lubricating coating coated on the surface of the fiber matrix; the metal-based self-lubricating coating comprises metal and a self-lubricating material.
[0020] In the present invention, the fiber matrix preferably includes carbon fiber. The present invention has no special requirements on the specifications of the carbon fiber. In an embodiment of the present invention, the fiber matrix is 12k carbon fiber or 24k carbon fiber.
[0021] In the present invention, the mass of the metal-based self-lubricating coating is preferably 20-60% of the mass of the self-lubricating conductive fiber; in specific embodiments, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0022] In the present invention, the metal-based self-lubricating coating comprises metal and self-lubricating material; the metal comprises one or more of nickel, copper, silver, aluminum and gold. In an embodiment of the present invention, the metal is nickel.
[0023] In the present invention, the self-lubricating material preferably includes one or more of graphite, molybdenum disulfide, tungsten disulfide and polytetrafluoroethylene; the particle size of the self-lubricating material is preferably less than 100nm. In the present invention, the mass of the self-lubricating material is preferably 0.5-2% of the mass of the self-lubricating conductive fiber; in specific embodiments, it can be 0.5%, 1%, 1.5% or 2%.
[0024] Figure 1 The schematic diagram of the structure of the self-lubricating conductive fiber of the present invention is shown in FIG. 1-1 is a fiber matrix, 1-2 is a metal-based self-lubricating coating, and 1-3 is a self-lubricating material in the metal-based self-lubricating coating.
[0025] In the related art, a metal layer is often plated on the surface of the fiber matrix. The present invention adds a self-lubricating material to the metal plating layer to ensure the conductivity of the plating layer and give it a self-lubricating function. The self-lubricating conductive fiber provided by the present invention will form a special friction structure on the friction surface during the friction and wear process to achieve the effect of anti-wear and friction reduction.
[0026] The present invention provides a method for preparing the self-lubricating conductive fiber described in the above scheme, comprising the following steps: The fiber matrix is placed in a metal plating solution containing a self-lubricating material and electroplated to obtain the self-lubricating conductive fiber.
[0027] Before the electroplating, the present invention preferably performs a pretreatment on the fiber matrix, and the pretreatment preferably includes: sequentially burning, cleaning with a cleaning agent, and washing with water on the fiber matrix.
[0028] In the present invention, the burning temperature is preferably 400-600°C, and the holding time is preferably 3-10 minutes; in a specific embodiment, the burning temperature can be 400°C, 450°C, 500°C, 550°C or 600°C, and the holding time can be 3 minutes, 5 minutes, 7 minutes or 10 minutes; the burning is preferably carried out under the condition of passing protective gas; the protective gas is preferably nitrogen or argon. The present invention causes the epoxy prepolymer on the fiber surface to gasify and escape through burning, so that the microscopic grooves originally coated on the fiber surface and distributed along the fiber axis are highlighted, providing an anchor point that is conducive to metal deposition and attachment.
[0029] In the present invention, the cleaning agent preferably includes, by mass percentage, 0.05-0.5% of a cationic surfactant, 0.5-2% of an organic amine, 0.5-6% of an alcohol and / or ether and / or alcohol ether, and the remainder is water.
[0030] In a specific embodiment, the content of cationic surfactant in the cleaning agent can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%; the content of organic amine can be 0.5%, 1%, 1.5% or 2%; the content of alcohol and / or ether and / or alcohol ether can be 0.5%, 1%, 2%, 3%, 4%, 5% or 6%.
[0031] In the present invention, the cationic surfactant preferably includes dodecylquinolinium bromide; the organic amine preferably includes polyethylene polyamine and / or diglycolamine; the alcohol preferably includes 2-amino-2-ethyl-1,3-propanediol; the alcohol ether preferably includes dipropylene glycol monomethyl ether; the ether preferably includes one or more of diether, aromatic ether and cyclic ether; the diether preferably includes dimethyl ether, the aromatic ether preferably includes phenyl ether, and the cyclic ether preferably includes tetrahydrofuran and / or ethylene oxide.
[0032] In the present invention, the cationic surfactant can combine with the non-polar substance on the fiber surface to play a role in cleaning, reducing surface tension, and improving the solid-liquid separation effect; organic amines, alcohols or ethers or alcohol ethers are all good solvents that can clean the dirt remaining on the fiber surface.
[0033] In the present invention, the cleaning agent is preferably obtained by mixing an aqueous solution of a cationic surfactant, an aqueous solution of an organic amine, an aqueous solution of an alcohol and / or an ether and / or an alcohol ether, and water; the mass concentration of the aqueous solution of the cationic surfactant is preferably 1-5%; the mass concentration of the aqueous solution of the organic amine is preferably 5-10%; the mass concentration of the aqueous solution of the alcohol and / or an ether and / or an alcohol ether is preferably 10-30%.
[0034] In the present invention, the cleaning temperature of the cleaning agent is preferably 40-60°C, and the cleaning time is preferably 1-5 minutes; in a specific embodiment, the cleaning temperature of the cleaning agent can be 40°C, 50°C or 60°C, and the cleaning time can be 1 minute, 2 minutes, 3 minutes, 4 minutes or 5 minutes. The present invention preferably places the calcined fiber matrix in a cleaning agent for cleaning. After calcination, there is still some sizing agent that has not been completely removed on the fiber surface. The present invention further removes the residual organic sizing agent by cleaning with a cleaning agent. At the same time, the cleaning agent contains cations that adhere to the surface of the fiber matrix, which is beneficial to the subsequent deposition and reduction of metal cations on the fiber surface and enhances the bonding strength between the coating and the fiber matrix.
[0035] After the cleaning with the cleaning agent is completed, the present invention preferably further comprises washing the cleaned fiber matrix with water.
[0036] In the present invention, the water washing temperature is preferably 45-55°C, and the washing time is preferably 1-5 minutes. In a specific embodiment, the water washing temperature can be 45°C, 50°C or 55°C, and the washing time can be 1 minute, 2 minutes, 3 minutes, 4 minutes or 5 minutes. The present invention ensures the cleanliness of the fiber matrix through water washing and prevents the introduction of reagents between different processes to cause metal plating solution contamination.
[0037] In the present invention, the concentration of the self-lubricating material in the metal plating solution is preferably 5-50 g / L, and in a specific embodiment, it can be 5 g / L, 10 g / L, 15 g / L, 20 g / L, 30 g / L, 40 g / L, 45 g / L or 50 g / L. The present invention does not specifically limit the composition of the plating solution, which is determined according to the type of metal to be plated. In the present invention, when the metal in the metal-based self-lubricating coating is nickel, the composition of the metal plating solution is preferably: nickel ion concentration in nickel sulfamate 70-110 g / L, boric acid 30-40 g / L, nickel chloride hexahydrate 3-15 g / L; or nickel sulfate hexahydrate 200-280 g / L, nickel chloride hexahydrate 15-30 g / L, boric acid 15-25 g / L.
[0038] The present invention has no special requirements for the electroplating conditions, which are determined according to the type of metal plating solution. When the metal plating solution is a nickel plating solution, the current density of the electroplating is preferably 1-5 A / dm 2 .
[0039] In the electroplating process of the present invention, metal cations are deposited and reduced on the fiber surface, and at the same time, the self-lubricating material is adsorbed onto the surface of the metal coating or embedded into the metal coating to form a metal-based self-lubricating coating.
[0040] After the electroplating is completed, the present invention preferably further comprises washing, drying and winding the obtained self-lubricating conductive fiber.
[0041] The present invention has no special requirements for the water washing, as long as the chemical reagents on the fiber surface can be cleaned.
[0042] In the present invention, the drying temperature is preferably 90-150°C, and the drying time is preferably 3-7 min; in a specific embodiment, the drying temperature can be 90°C, 110°C, 130°C or 150°C, and the drying time can be 3 min, 4 min, 5 min, 6 min or 7 min.
[0043] Figure 2 FIG. 1 is a schematic diagram of the preparation process of the self-lubricating conductive fiber in an embodiment of the present invention. Figure 2 As shown, the fiber matrix in the fiber pay-off device 1 is flattened by the fiber flattening device 2 and then enters the high-temperature oven 3 for burning. The fiber matrix after burning is sent to the cleaning tank 5 through the first transmission guide roller 4 for cleaning with a cleaning agent, and then sent to the first water washing tank 7 through the second transmission guide roller 6 for water washing. The fiber matrix after water washing is sent to the electroplating tank 10 through the third transmission guide roller 8 for electroplating to form a metal-based self-lubricating coating, and then sent to the second water washing tank 12 for water washing through the fourth transmission guide roller 11. The self-lubricating conductive fiber after water washing enters the drying oven 13 for drying treatment, and finally is taken up by the take-up device 14. In particular, 8 and 11 are conductive rollers, which are connected to the negative electrode 9 of the DC power supply as cathodes.
[0044] The self-lubricating conductive fiber and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] Example 1: Preparation of a nickel-based self-lubricating fiber based on 12k carbon fiber (1) The raw material 12k carbon fiber tow is orderly transported to the fiber flattening device through the pay-off device, and then transported to the high-temperature oven for burning; the burning temperature is 500°C, the treatment time is 5 minutes, the protective gas nitrogen is introduced, and the gas flow rate is 300sccm. The treated fiber is continuously transported to the cleaning tank for step (2); (2) The composition of the cleaning agent is: in addition to pure water, it contains 5% of dodecyl quinoline bromide with a mass concentration of 3%, 15% of polyethylene polyamine with a mass concentration of 10%, and 20% of dipropylene glycol monomethyl ether with a mass concentration of 12%. The solution temperature is set to 50°C and the cleaning time is 3 minutes. The cleaned fiber is continuously transported to step (3); (3) The fiber washed in step (2) is washed in 50°C warm water for 2 min to ensure cleanliness and prevent the reagents from being brought in between different processes and causing contamination of the bath solution. The fiber is then continuously transported to step (4); (4) A nickel-based self-lubricating plating solution is set in the plating tank, and a nickel sulfamate plating solution is used, that is, the main salt is nickel sulfamate, and molybdenum disulfide is added to the plating solution as a self-lubricating material with a concentration of 13g / L. The specific process is: the current density is 3A / dm 2 , pH 3.8-4.2, temperature 50°C, nickel ion concentration in nickel sulfamate 95g / L, boric acid concentration 40g / L, nickel chloride hexahydrate concentration 3g / L, and the mass fraction of the coating is controlled to be 45% of the mass of the self-lubricating conductive fiber. The electroplated fiber is continuously transported to step (5); (5) The electroplated fiber was washed again and then dried at a temperature of 120°C for 4 min. Finally, a take-up device was used to collect the finished self-lubricating conductive fiber. The mass of molybdenum disulfide in the coating accounted for 0.8% of the mass of the self-lubricating conductive fiber.
[0046] The 12k nickel-based self-lubricating carbon fiber wire prepared by the above process has a resistance of 1.3Ω / m. When it is assembled into a conductive ring and used in an air-cooled variable frequency motor, the test speed is 18000rpm, the friction shaft diameter is 25mm, the friction time is 800h, and the fiber wear length on the conductive ring is 0.0023mm, which can meet the vehicle's 800,000 kilometers of driving without maintenance or replacement, indicating that the fiber has good friction reduction and wear resistance.
[0047] Three samples of the self-lubricating conductive fiber prepared in Example 1 were subjected to a hot and cold cycle test. The fibers were placed in an oven preheated to 180°C and kept for 30 minutes. After the fibers were taken out of the oven, they were placed in a low-temperature box precooled to -65°C within 3 minutes and kept for 30 minutes. The cycle was repeated three times. After the test, the resistance change was <+0.30Ω / m, indicating that the metal layer on the fiber surface had good bonding strength.
[0048] Table 1 Hot and cold cycle test results of Example 1
[0049] Example 2: Preparation of a nickel-based self-lubricating fiber based on 24k carbon fiber (1) The raw material 24k carbon fiber tow is orderly transported to the fiber flattening device through the pay-off device, and then transported to the high-temperature oven for burning; the burning temperature is 500°C, the treatment time is 5 minutes, the protective gas nitrogen is introduced, and the gas flow rate is 300sccm. The treated fiber is continuously transported to the cleaning tank for step (2); (2) The composition of the cleaning agent is: in addition to pure water, it contains 8% of 5% dodecyl quinoline bromide, 20% of 10% polyethylene polyamine, and 15% of 20% dipropylene glycol monomethyl ether. The solution temperature is set to 50°C and the cleaning time is 4 minutes. The cleaned fiber is continuously transported to step (3); (3) The fiber washed in step (2) is washed in 50°C warm water for 3 min to ensure cleanliness and prevent the reagents from being brought in between different processes and causing contamination of the bath solution. The fiber is then continuously transported to step (4); (4) A nickel-based self-lubricating plating electrolyte is set in the electroplating tank, and an aminosulfonic acid nickel plating solution is used, that is, the main salt is aminosulfonic acid nickel, and polytetrafluoroethylene is added to the plating solution as a self-lubricating material with a concentration of 13g / L. The specific process is: the current density is 3A / dm 2 , pH 3.8-4.2, temperature 55°C, nickel ion concentration in nickel sulfamate 95g / L, boric acid concentration 40g / L, nickel chloride hexahydrate concentration 3g / L, and the mass fraction of the coating is controlled to be 53% of the mass of the self-lubricating conductive fiber. The electroplated fiber is continuously transported to step (5); (5) The electroplated fibers were washed again and then dried at a temperature of 130°C for 5 min. Finally, a take-up device was used to collect the finished self-lubricating conductive fibers. The mass of molybdenum disulfide in the coating was 1.1% of the mass of the self-lubricating conductive fibers.
[0050] The 24k nickel-based self-lubricating carbon fiber wire prepared by the above process has a resistance of 0.52Ω / m. When it is assembled into a conductive ring and used in an air-cooled variable frequency motor, the test speed is 18000rpm, the friction shaft diameter is 25mm, the friction time is 800h, and the fiber wear length on the conductive ring is 0.0013mm, which can at least meet the vehicle's driving of 800,000 kilometers without maintenance or replacement, indicating that the fiber has good friction reduction and wear resistance.
[0051] Three samples of the self-lubricating conductive fiber were taken for hot and cold cycle test. The fibers were placed in an oven preheated to 180°C and kept for 30 minutes. After the fibers were taken out of the oven, they were placed in a low-temperature box precooled to -65°C within 3 minutes and kept for 30 minutes. The cycle was repeated three times. After the test, the resistance change was ≤+0.12Ω / m, indicating that the metal layer on the fiber surface has good bonding strength.
[0052] Table 2 Hot and cold cycle test results of Example 2
[0053] Comparative Example 1: The only difference from Example 1 is that step (2) is not performed, and the rest of the process is the same.
[0054] The 12k nickel-based self-lubricating carbon fiber wire prepared in Comparative Example 1 has a resistance of 1.3Ω / m. When it is assembled into a conductive ring and used in an air-cooled variable frequency motor, the test speed is 18000rpm, the friction shaft diameter is 25mm, the friction time is 800h, and the fiber wear length on the conductive ring is 0.0041mm. The fiber's friction reduction and wear resistance performance is reduced.
[0055] Three samples of the fiber obtained in Comparative Example 1 were subjected to a hot and cold cycle test. The fiber was placed in an oven preheated to 180°C and kept for 30 minutes. After the fiber was taken out of the oven, it was placed in a low-temperature box precooled to -65°C within 3 minutes and kept for 30 minutes. The cycle was repeated three times. After the test, the resistance change was ≤+0.50Ω / m, indicating that the bonding strength of the metal layer on the fiber surface decreased.
[0056] Table 3 Hot and cold cycle test results of comparative example 1
[0057] Comparative Example 2: The only difference from Example 1 is that the plating solution does not contain self-lubricating material, and the rest of the process is the same.
[0058] The resistance of the 12k nickel-plated carbon fiber wire prepared in Comparative Example 2 is 1.2Ω / m. When it is assembled into a conductive ring and used in an air-cooled variable frequency motor, the test speed is 18000rpm, the friction shaft diameter is 25mm, the friction time is 800h, and the fiber wear length on the conductive ring is 0.0158mm. The fiber's friction reduction and wear resistance performance is significantly reduced.
[0059] The above-mentioned fiber was subjected to a hot and cold cycle test. The fiber was placed in an oven preheated to 180°C and kept for 30 minutes. After the fiber was taken out of the oven, it was placed in a low-temperature box precooled to -65°C within 3 minutes and kept for 30 minutes. The cycle was repeated three times. After the test, the resistance change was ≤+0.30Ω / m, indicating that the metal layer on the fiber surface had good bonding strength.
[0060] Table 4 Hot and cold cycle test results of comparative example 2
[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A self-lubricating conductive fiber, characterized in that: It comprises a fiber matrix and a metal-based self-lubricating coating coated on the surface of the fiber matrix; the metal-based self-lubricating coating comprises metal and self-lubricating material.
2. The self-lubricating conductive fiber according to claim 1, characterized in that: The fiber matrix includes carbon fibers.
3. The self-lubricating conductive fiber according to claim 1, characterized in that: The metal includes one or more of nickel, copper, silver, aluminum and gold.
4. The self-lubricating conductive fiber according to claim 1, characterized in that: The self-lubricating material includes one or more of graphite, molybdenum disulfide, tungsten disulfide and polytetrafluoroethylene.
5. The self-lubricating conductive fiber according to any one of claims 1 to 4, characterized in that: The mass of the metal-based self-lubricating coating is 20-60% of the mass of the self-lubricating conductive fiber; the mass of the self-lubricating material is 0.5-2% of the mass of the self-lubricating conductive fiber.
6. The method for preparing the self-lubricating conductive fiber according to any one of claims 1 to 5, characterized in that: The following steps are involved: The fiber matrix is placed in a metal plating solution containing a self-lubricating material and electroplated to obtain the self-lubricating conductive fiber.
7. The preparation method according to claim 6, characterized in that: Before the electroplating, the fiber matrix is also pre-treated, and the pre-treatment includes: burning the fiber matrix and cleaning it with a cleaning agent in sequence.
8. The preparation method according to claim 7, characterized in that: The burning temperature is 400-600° C., and the heat preservation time is 3-10 minutes; the burning is carried out under the condition of passing protective gas.
9. The preparation method according to claim 7, characterized in that: Calculated by mass percentage, the cleaning agent includes 0.05-0.5% of a cationic surfactant, 0.5-2% of an organic amine, 0.5-6% of an alcohol and / or an ether and / or an alcohol ether, and the balance is water.
10. The preparation method according to claim 9, characterized in that: The cationic surfactant includes dodecylquinolinium bromide; the organic amine includes polyethylene polyamine and / or diglycolamine; the alcohol includes 2-amino-2-ethyl-1,3-propanediol; the alcohol ether includes dipropylene glycol monomethyl ether; and the ether includes one or more of diether, aromatic ether and cyclic ether.
Citation Information
Patent Citations
Apparatus and method for continuously composite plating metallic and nano particle on carbon fiber surface
CN101250735A
Device and method for continuously compounding plating metal and nano-particles on surface of carbon fiber
CN102031547A